CoSe2/MoS2 Heterostructures to Couple Polysulfide Adsorption and Catalysis in Lithium‐Sulfur Batteries†. Issue 5 (13th April 2021) - Shen, Zihan; Zhou, Qingwen; Yu, Huiling; Tian, Jiaming; Shi, Man; Hu, Chaoquan; Zhang, Huigang
Main observation and conclusion: Lithium‐sulfur batteries have been regarded as one of most promising next‐generation energy storage devices because of their high energy density and low cost. However, polysulfide shuttling and slow kinetics hinder the practical application. We fabricated hierarchically heterostructured CoSe2 /MoS2 nanoarrays on carbon clothes as the sulfur cathode host. The resulting heterostructures facilitate electron conduction and improve electrolyte wetting. More importantly, the composite heterostructures couple the strong polysulfide adsorption of CoSe2 and high catalytic activity of MoS2 to synergistically accelerate polysulfide conversion, demonstrating higher catalytic activity than their individual components. Abstract : CoSe2 /MoS2 heterostructures couple the strong polysulfide adsorption of CoSe2 and high catalytic activity of MoS2 to synergistically accelerate polysulfide conversion, demonstrating higher catalytic activity than their individual components.